Sunset Boulevard - Brackett, Charles 1892-1969; Holden, William 1918-1981; Marshman, D. M 1922-; Swanson, Gloria; Von Stroheim, Erich, \d 1885-1957; Wilder, Billy 1906-2002; Paramount Pictures Corporation (Hollywood, Calif Paramount Pictures, 2002)
Pursued by creditors, Joe swerves into a driveway of a seemingly abandoned Sunset Boulevard mansion. He finds Norma, an ex-screen queen dreaming of a dramatic comeback and her husband/servant living there. She takes a fancy to Joe and, learning that he is a scriptwriter, persuades him to help her with her comeback screenplay. Being broke he accepts. He falls in love with a young script reader, but Norma breaks up their romance. Thinking she is mad, he tries to leave, but Norma kills him in a scene which she believes is the highlight of her comeback movie
Originally released as a motion picture in 1950
Special features: Commentary by Ed Sikov, author of "On Sunset Boulevard: the life and times of Billy Wilder" ; a 28 min. documentary, Sunset Blvd., a look back (c2002) ; theatrical trailer ; Hollywood location map ; photo galleries ; morgue prologue ; Edith Head - The Paramount Years (featurette) ; The music of Sunset Boulevard (featurette)
Cinematographer, John F. Seitz ; editors, Doane Harrison, Arthur Schmidt ; music, Franz Waxman ; costume designer, Edith Head
William Holden, Gloria Swanson, Erich Von Stroheim, Nancy Olsen, Fred Clark, Lloyd Gough, Jack Webb, Cecil B. DeMille, Hedda Hopper, Buster Keaton
DVD, Dolby digital mono, Region 1 encoding
1
Keywords: Actors -- Drama; Motion picture industry -- Drama; Hollywood (Los Angeles, Calif.) \v Drama; Feature films \z United States; Feature films; Video recordings for the hearing impaired